ChemInform Abstract: Alkene‐Assisted Nickel‐Catalyzed Regioselective 1, 4‐Addition of Organoboronic Acid to Dienones: A Direct Route to All‐Carbon Quaternary Centers. Issue 48 (2nd December 2014) - Hong, Ya‐Chun; Gandeepan, Parthasarathy; Mannathan, Subramaniyan; Lee, Wei‐Tse; Cheng, Chien‐Hong
Abstract A nickel‐catalyzed, highly regioselective conjugate addition of boronic acids to dienones to form 1, 4‐addition products with an all‐carbon quaternary center is described.